2021
DOI: 10.3390/cryst11010047
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Applications of Graphene-Based Nanocomposites in Clean Energy Materials

Abstract: Extensive use of fossil fuels can lead to energy depletion and serious environmental pollution. Therefore, it is necessary to solve these problems by developing clean energy. Graphene materials own the advantages of high electrocatalytic activity, high conductivity, excellent mechanical strength, strong flexibility, large specific surface area and light weight, thus giving the potential to store electric charge, ions or hydrogen. Graphene-based nanocomposites have become new research hotspots in the field of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 151 publications
0
14
0
Order By: Relevance
“…In the field of energy storage and conversion, graphene-based nanocomposites have emerged as a new research topic. Graphene has been further changed as a catalyst carrier for hydrogen fuel cells to provide a more excellent uniform metal dispersion, therefore enhancing the electrocatalyst activity [93]. The high-performance-based A-site layered (SmBaMnO 5+δ , SBM) perovskite has been synthesized by the combustion method.…”
Section: Nanoscale Based Electrode Catalysts For Fuel Cellsmentioning
confidence: 99%
“…In the field of energy storage and conversion, graphene-based nanocomposites have emerged as a new research topic. Graphene has been further changed as a catalyst carrier for hydrogen fuel cells to provide a more excellent uniform metal dispersion, therefore enhancing the electrocatalyst activity [93]. The high-performance-based A-site layered (SmBaMnO 5+δ , SBM) perovskite has been synthesized by the combustion method.…”
Section: Nanoscale Based Electrode Catalysts For Fuel Cellsmentioning
confidence: 99%
“…(Chang et al, 2016). The chemical structure of GO is redrawn as shown in Figure 1 (Xiang et al, 2021).…”
Section: Structural Analysis Of Graphene Nanocompositesmentioning
confidence: 99%
“…Chemical structure of graphene oxide with its chemical analysis redrawn using ChemDraw ultra 12 (Xiang et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…7 It has become highly desirable to develop a convenient and cost-effective technology for graphene synthesis, especially from waste biomass or non-fossil fuel. 8,9 Studies have shown that the activation process is a plausible graphene synthesis method, which can both increase the surface area and acquire well-developed porosity. 10,11 The conversion of the disordered structure of biochar into a graphite structure can be attributed to the carbide formation-decomposition mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are still costly for on‐scale production owing to the high price of graphite and their unsustainable properties 7 . It has become highly desirable to develop a convenient and cost‐effective technology for graphene synthesis, especially from waste biomass or non‐fossil fuel 8,9 …”
Section: Introductionmentioning
confidence: 99%